2022
DOI: 10.33200/ijcer.1123204
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Using Model and Augmented Reality Technology on Students’ Science Achievement, Motivation, and Interest Levels

Abstract: In this study, it was aimed to investigate the effects of modelling and the material designed with augmented reality technology on the academic success of students, their motivation, and interest levels towards the science course. The study was conducted in 6th grade science units of "Support and Movement System" and "Systems in Our Body". In the study, quasi-experimental design with pre-test post-test control group was applied. The study was carried out with three groups: the control group, the augmented real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Source: (Hong et al, 2018) From the 29 selected articles, a diverse array of research designs was identified. Among them, 11 studies adopted quantitative non-randomized research designs (Al-Muqbil, 2022; Damopolii et al, 2022;Gnidovec et al, 2020;Gregorcic & Torkar, 2022;Lam et al, 2023;Nurhayati et al, 2022;Petrov & Atanasova, 2020;Sivri & Eroglu, 2022;Stojšić, Ostojić, & Stanisavljević, 2022;Weng et al, 2020a;Yang & Tsai, 2021). An equal number of studies, 11 in total, utilized mixed-method research designs (Celik et al, 2020;Delgado-Rodríguez, Carrascal Domínguez, & Garcia-Fandino, 2023;Erbas & Demirer, 2019;Fuchsova & Korenova, 2019;Kozcu Cakir et al, 2020;Lo et al, 2021;Omurtak & Zeybek, 2022;Serdar Yıldırım, 2021;Yapici & Karakoyun, 2021;Yildirim, 2020;Ziden et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Source: (Hong et al, 2018) From the 29 selected articles, a diverse array of research designs was identified. Among them, 11 studies adopted quantitative non-randomized research designs (Al-Muqbil, 2022; Damopolii et al, 2022;Gnidovec et al, 2020;Gregorcic & Torkar, 2022;Lam et al, 2023;Nurhayati et al, 2022;Petrov & Atanasova, 2020;Sivri & Eroglu, 2022;Stojšić, Ostojić, & Stanisavljević, 2022;Weng et al, 2020a;Yang & Tsai, 2021). An equal number of studies, 11 in total, utilized mixed-method research designs (Celik et al, 2020;Delgado-Rodríguez, Carrascal Domínguez, & Garcia-Fandino, 2023;Erbas & Demirer, 2019;Fuchsova & Korenova, 2019;Kozcu Cakir et al, 2020;Lo et al, 2021;Omurtak & Zeybek, 2022;Serdar Yıldırım, 2021;Yapici & Karakoyun, 2021;Yildirim, 2020;Ziden et al, 2022).…”
Section: Methodsmentioning
confidence: 99%